Actor-network Theory and cartography of controversies in Information Science (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2019)
The present study aims to discuss the interactions between the Actor-network Theory and the Cartography of Controversies method in Information Science research. A literature review was conducted on books, scholarly articles, and any other sources addressing the Theory-Actor Network and Cartography of Controversies. The understanding of the theoretical assumptions that guide the Network-Actor Theory allows examining important aspects to Information Science research, seeking to identify the relationships between information, people, and technological equipment in the structure of information flows that create intricate information sharing networks. This interaction between the Actor-network theory and Information Science highlights the role of the research method Cartography of Controversies as an approach that results from the use of the Actor-network theory to investigate the creation of sociotechnical networks.Keywords: Actor-network theory. Cartography of controversies. Information science.Link: http://www.scielo.br/pdf/tinf/v30n1/2318-0889-tinf-30-1-0121.pdf